Exploration of biomarkers for efficacy evaluation of traditional Chinese medicine syndromes of acute exacerbation of chronic obstructive pulmonary disease based on metabolomics - Hailong, Zhang; Yimei, Si; Yan, Du; Xinguang, Liu; Jiansheng, Li (Frontiers in Pharmacology, 2024)
Background: Traditional Chinese medicine (TCM) is effective for the treatment of acute exacerbation of chronic obstructive pulmonary disease (AECOPD); however, there is no objective index for the evaluation of TCM syndrome efficacy. This study aimed to screen biomarkers related to the efficacy of TCM syndrome using metabolomics. We recruited AECOPD patients with phlegm-heat congesting lung (PH)/ phlegm-damp amassing lung (PD) syndrome and treated them with Chinese herbal medicine (Qingre Huatan or Zaoshi Huatan granules) in addition to conventional medicine for 7 days. Data on clinical symptoms and sign scores, modified British Medical Research Council (mMRC), COPD assessment test (CAT), and inflammation indicators, including white blood cell (WBC) count, percentage of neutrophil count (NEU%), and C-reactive protein (CRP), were collected before and after treatment to evaluate the therapeutic effect. Serum samples were collected before and after treatment for metabolomic analysis to screen differential metabolites. Results: A total of 69 patients with AECOPD were enrolled, including 41 and 28 patients in the PH and PD groups, respectively. The clinical symptoms and sign scores, CAT, mMRC, NEU%, and CRP levels after treatment were lower than those before treatment in both groups (P<0.05). Serum metabolomics analysis showed that there were 13 differential metabolites in the PH group and 16 differential metabolites in the PD group before and after treatment (P < 0.05, variable importance projection (VIP) ≥ 1.00). In the PH group, lysophosphatidylcholine (LPC) (16:0), LPC (17:1), LPC (18:3), LPC (18:2), and LPC (17:0) negatively correlated with clinical symptoms and sign scores (P < 0.05); LPC (16:0), LPC (17:1), LPC (16:1), and LPC (17:0) negatively correlated with WBC (P < 0.05) and NEU% (P < 0.05); and LPC (16:0) negatively correlated with CRP levels. In the PD group, L-phenylalanine positively correlated with CRP levels (P < 0.05), and 2-methylbutyroylcarnitine positively correlated with clinical symptoms and sign (P < 0.05) and CAT scores (P < 0.05). DL-carnitine positively correlated with clinical symptoms and sign scores (P < 0.05). Serum metabolites may be potential indicators to objectively evaluate the efficacy of TCM syndromes; however, further large controlled trials are required to verify these findings.